Investigation on Soil Erodibility Under Different Land Use Patterns of Certain Soils of Sub-Montane Punjab, India - Kahlon, M. S. (Indian Forester, 2006)
The assessment of soil erodibility is essential to understand the mechanism of soil erosion and in preparing soil erodibility maps required in land use planning. Soil erosion, a serious problem in sub-montane Punjab, India was intensively studied in the present investigation. Soil erodibility was assessed through erodibility indices, nomographic technique and under simulated rainfall conditions. The erosion ratio and dispersion ratio values of the forest and grasslands were generally lower than those of arable and bare lands. The forest soils had better physical condition with respect to aggregation, infiltration and organic matter content. Erosion ratio and dispersion ratio values decreases from 99.5 to 71.5 and 91.4 to 78.8 under bare and forested condition respectively. Erodibility appears to be significantly and directly related to dispersion ratio. Under simulated rainfall conditions, the run-off and soil loss was also observed to be least under forest and grasslands. Run-off, soil loss and soil erodibility (k) decreases from 71.4 to 54.4(%), 51.3 to 31.3 (t/ha) and 0.45 to 0.27 under bare and forested conditions respectively. Soil erodibility evaluated through nomographic technique showed lesser k value under forest and grass land use as compared to arable and bare soils.